Moving the needle on fall prevention: A Geriatric Emergency Care Applied Research (GEAR) Network scoping review and consensus statement. (15th June 2021) - Hammouda, Nada; Carpenter, Christopher R.; Hung, William W.; Lesser, Adriane; Nyamu, Sylviah; Liu, Shan; Gettel, Cameron J.; Malsch, Aaron; Castillo, Edward M.; Forrester, Savannah; Souffront, Kimberly; Vargas, Samuel; et al.
Abstract: Background: Although falls are common, costly, and often preventable, emergency department (ED)‐initiated fall screening and prevention efforts are rare. The Geriatric Emergency Medicine Applied Research Falls core (GEAR‐Falls) was created to identify existing research gaps and to prioritize future fall research foci. Methods: GEAR's 49 transdisciplinary stakeholders included patients, geriatricians, ED physicians, epidemiologists, health services researchers, and nursing scientists. We derived relevant clinical fall ED questions and summarized the applicable research evidence, adhering to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses for Scoping Reviews. The highest‐priority research foci were identified at the GEAR Consensus Conference. Results: We identified two clinical questions for our review (1) fall prevention interventions (32 studies) and (2) risk stratification and falls care plan (19 studies). For (1) 21 of 32 (66%) of interventions were a falls risk screening assessment and 15 of 21 (71%) of these were combined with an exercise program or physical therapy. For (2) 11 fall screening tools were identified, but none were feasible and sufficiently accurate for ED patients. For both questions, the most frequently reported study outcome was recurrent falls, but various process and patient/clinician‐centered outcomes were used. Outcome ascertainment relied on self‐reported falls in 18 of 32 (56%) studies for (1) and nine of 19 (47%) studies for (2). Conclusion: Harmonizing definitions, research methods, and outcomes is needed for direct comparison of studies. The need to identify ED‐appropriate fall risk assessment tools and role of emergency medical services (EMS) personnel persists. Multifactorial interventions, especially involving exercise, are more efficacious in reducing recurrent falls, but more studies are needed to compare appropriate bundle combinations. GEAR prioritizes five research priorities: (1) EMS role in improving fall‐related outcomes, (2) identifying optimal ED fall assessment tools, (3) clarifying patient‐prioritized fall interventions and outcomes, (4) standardizing uniform fall ascertainment and measured outcomes, and (5) exploring ideal intervention components.